Enhanced Homestead Food Production LLUS+ Program in the Lake Zone, Tanzania - Rawat, Rahul; Smith, Erin (International Food Policy Research Institute, 2014)
The purpose of this study is to assess if the Enhanced Homestead Food Production Plus (EHFP+) Program implemented by HKI in Mwanza, Tanzania, enhances uptake of Micronutrient Powder (MNP) supplementation in children, helps maintaining reduced anemia levels among children after a blanket provision of MNP, and has an impact on child growth, infant and young child feeding (IYCF) practices, maternal knowledge related to health, nutrition, WASH and malaria prevention, food security and women's empowerment.